Oxadiazole derivatives: Histone deacetylase inhibitors in anticancer therapy and drug discovery - Balaji Wamanrao Matore; Purusottam Banjare; Tanmoy Guria; Partha Pratim Roy; Jagadish Singh (Elsevier, 2022)
Heterocycles are being playing an important role in cancer treatment for years. Currently, a number of anticancer agents are available on market, but concerns such as less effectiveness, drug resistance, adverse effects, and non-selectivity create an urgent need for the development of newer highly potent anticancer agents with fewer side effects. Among the heterocycles, oxadiazole is of great interest in the recent era due to their potential anticancer activity. Structurally, oxadiazole is a five-member heterocyclic ring that contains one oxygen and two nitrogen heteroatom. The important mechanism of cancer cell suppression involve the inhibition of different growth factors and enzymes including histone deacetylase (HDAC), thymidylate synthase (TS), vascular endothelial growth factor (VEGF), glycogen synthase kinase-3 (GSK), epidermal growth factor (EGF), and etc. HDAC is considered a potential drug target in cancer therapy and drug discovery. HDAC inhibitors act by promoting acetylation of histones, regulate and cause cancer cell death by different pathways, like apoptosis, differentiation, cell cycle arrest and inhibition of DNA repair, up-regulation or reactivation of silenced tumor suppressors, and down regulation of growth factors. Recently, five drugs namely Vorinostat (SAHA), Romidepsin (FK-228), Belinostat (PXD-101), Panobinostat (LBH-589), and Chidamide have been granted by US/Chinese FDA for cancer treatment and several are in the queue of clinical trials. The focused area of this review is to summarize the current status, chemistry, structure activity relationship, mechanism of action, therapeutic potential of various oxadiazole derivatives as novel anticancer agents by inhibiting HDAC enzymes. Finally, we highlighted the future prospects of oxadiazole derivatives as anticancer agents.